Coincidence points of mappings and relations with applications - Azam, Akbar (Fixed point theory and algorithms for sciences and engineering, 2012)
We obtain coincidence points of mappings and relations under a contractive condition in a metric space. As applications, we achieve an existence and uniqueness theorem of solution for a general class of nonlinear integral equations. 2010 Mathematics Subject Classification: 47H10; 54H25; 54C60.